2012
DOI: 10.1016/j.visres.2012.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Standardized F1 – A consistent measure of strength of modulation of visual responses to sine-wave drifting gratings

Abstract: The magnitude of spike-responses of neurons in the mammalian visual system to sine-wave luminance-contrast-modulated drifting gratings is modulated by the temporal frequency of the stimulation. However, there are serious problems with consistency and reliability of the traditionally used methods of assessment of strength of such modulation. Here we propose an intuitive and simple tool for assessment of the strength of modulations in the form of standardized F1 index, zF1. We define zF1 as the ratio of the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 60 publications
1
25
0
Order By: Relevance
“…The discharge-rate spectral RFs provide information about the spatiotemporal properties of the neurons [12], [15], [49][53], while F1 spectral RFs bring information about their phase sensitivity [53]. Since F1 depends on the magnitude of the response, we have used standardized F1 values [40] to plot spectral RFs.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The discharge-rate spectral RFs provide information about the spatiotemporal properties of the neurons [12], [15], [49][53], while F1 spectral RFs bring information about their phase sensitivity [53]. Since F1 depends on the magnitude of the response, we have used standardized F1 values [40] to plot spectral RFs.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies revealed stimulus-dependent modulations of neuronal activity in the SC [15], [40], [62], LP-Pul complex [35], Sg [16], [40], as well as from the lateral most part of the AES cortex (insular cortex) [37], and the CN [36], [40]. However, to our knowledge, there are no studies that have examined modulatory spectral RFs or compared spatial and temporal frequencies in response to an optimal stimulus in terms of discharge rate versus those maximizing modulations in the extrageniculate visual system.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations